The Influence of Training, Competency, and Motivation on the Performance of the Office of the Djalaluddin Airport Operational Unit of Gorontalo - Supri; Titin Dunggio; Lisda Van Gobel (LP2M Universitas Bina Mandiri Gorontalo, 2020)
The objectives of this study were: 1) to determine and analyze the effect of training on employee performance in the Office of the Djalaluddin Airport Operational Unit of Gorontalo; 2) to determine and analyze the influence of competence on employee performance in the Office of the Djalaluddin Airport Operational Unit of Gorontalo; 3) to determine and analyze the influence of motivation on employee performance in the Office of the Djalaluddin Airport Operational Unit of Gorontalo; 4) to identify and analyze the effect of training, competence and motivation simultaneously on employee performance in the Office of the Djalaluddin Airport Operational Unit of Gorontalo. This research uses quantitative research methods with observation data collection techniques, interviews, questionnaires, literature study and literature review. The data analysis technique used the SPSS 20 program, namely validity test, reliability test, classical assumption test and multiple linear regression analysis. The results of the research that the researchers conducted show that: 1) there is a positive and significant influence between training variables on employee performance in the office; 2) there is a positive and significant influence between competency variables on employee performance in the Office of the Djalaluddin Airport Operational Unit of Gorontalo; 3) there are positive and significant influence between motivation variables on employee performance in the Office of the Djalaluddin Airport Operational Unit of Gorontalo; 4) there is a positive and significant influence simultaneously between training, competence and motivation on employee performance at the Office of the Djalaluddin Airport Operational Unit of Gorontalo.